Aprendizagem de funções por meio da modelagem matemática: um estudo do comportamento de um composto químico - Fontes, Felipe Augusto Martinazzo (Universidade Federal de São Carlos, 2014)
The aim of this work is to propose the mathematical modeling use in the problems resolution, specially the study of the process of the chemical compounds in some drugs in the human body. Our study intends to answer questions as How long the drugs could be in our body? For answering these questions we proposed and made an activity with high school students from a private school.
Keywords: Modelagem matemática; Química; Função (Matemática); Mathematics; Chemistry; Function; CIENCIAS EXATAS E DA TERRA